Protein, methionine+cystine and lysine levels for Japanese quails during the production phase - Garcia, Edivaldo Antonio [UNESP]; Mendes, AA; Pizzolante, CC; Saldanha, ESPB; Moreira, J [UNESP]; Mori, C [UNESP]; Pavan, AC [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2005)
An experiment was conducted at Faculdade de Medicina Veterinária e Zootecnia/Unesp - Botucatu for 168 days to evaluate the effects of protein, Met + Cys and lysine diet levels on egg production and egg quality of laying Japanese quails. Quails with 42 days of age were reared in a completely randomized design. There were 1,944 quails distributed in four replicates of 27 birds per pen, according to a factorial 3x3x2 with three crude protein levels (16, 18 and 20% CP), three Met + Cys levels (0.700; 0.875 and 1.050%) and two lysine levels (1.100 and 1.375%). Birds fed diets with 18 and 20% CP had higher feed intake and egg production than those fed diets with 16% CP. There was significant interaction (p<0.05) between protein and Met + Cys levels on egg weight. There was no effects (p>0.05) of the protein level on feed conversion per dozen eggs; however, improved feed conversion per egg mass was seen for birds fed diets with 20% CP compared to those fed diets with 16% and 18% CP. Protein and lipid percentage in the yolk increased when dietary protein level increased from 16 to 18%. Increasing Met + Cys from 0.700% to 0.875% reduced yolk protein percentage. Higher lipid percentage in the yolk was seen in eggs from quails fed diets with 1.050% Met + Cys, whereas 1.375% lysine in the diet of resulted in decreased egg production and egg mass, besides poorer feed conversion per dozen eggs and per egg mass.
Keywords: egg production; egg quality; Lysine; Methionine+Cystine; protein; quails